Incongruencia jurídica entre el codigo organico de la funcion judicial, la constitución de la república del ecuador y los tratados internacionales respecto a la función de los abogados - Granda Iñiguez, Wilson Fernando (2016)
In Havana from 27 August to 7 September 1990, took place the 7th Congress of the United Nations on crime prevention and the treatment of offenders, in the they discussed and eventually approved "Basic principles on the role of lawyers, formulated to assist Member States in their task of promoting and ensuring the proper role of lawyers"which according to the text of the Treaty itself "should be taken into account and respected by the national Governments within the framework of its legislation and practice, and should bring to the attention of lawyers and other people such as judges, prosecutors, members of the Executive and legislative powers and the public in general." "Said agreement international, norman than lawyers do not suffer or are exposed to persecution or administrative, economic sanctions or other as a result of any action taken in accordance with the obligations, rules and ethical standards that are recognised at their profession". This is in contradiction with the organic code of the Judicial function, which instructs the punishing lawyers in Art. 26 specifically, power given to the Council of the judiciary. 5 This is violating the Constitution, since according to Magna Carta, in its article 181, the role of punishing lawyers is not competent. What legislator, with a minimum of enlightenment on the subject, seem him possible to provide audit powers to a body that belongs to another area, that act as Argentinean entity quality moral, intellectual and lawyer professional thus? Because only lawyers who have never exercised the profession or failing that they ignore the very essence of noble activity. They forget who adopted the organic code of the Judicial function which is the law which must comply with the Constitution and any way, is the other way round. Certainly laws develop constitutional principles but keeping full compliance with respect to them. This violates provisions of article 26 of the basic principles on the role of lawyers, who said: "The legislation or the profession legal through its appropriate bodies, establish codes of professional conduct for lawyers, in accordance with the laws and customs of the country and the rules and recognized international standards".